MAGNETOCLIMATOLOGY: TELECONNECTION BETWEEN THE SIBERIAN LOESS RECORD AND NORTH ATLANTIC HEINRICH EVENTS - Evans M.E.; Rutter N.W.; Catto N.; Chlachula J.; Nyvlt D. (My University, 2003)
New environmental magnetic data from loess and paleosol successions in outcrops in the upper reaches of the Ob River drainage, southern Siberia, track the major climatic variations over the last glacial-interglacial cycle. Profiles of magnetic susceptibility and alternating deposition of loess and soil-formation events correspond to oxygen isotope stages 1 5. The magnetic-susceptibility data, in association with the stratigraphic succession, confirm that the wind-vigor magnetoclimatological model is a viable alternative to the classic pedogenic model. Interpretation of magnetic-susceptibility data from loess- paleosol successions must therefore consider eolian dynamics, available source materials, and transport directions, in addition to pedogenic processes. Rapid magnetic fluctuations are also observed. These are identified—for the first time in Siberian records—as the signature of the abrupt cold pulses responsible for the Heinrich layers in North Atlantic marine sediments. The data thus form a component of climatic teleconnections across the Northern Hemisphere, allowing correlations to be made among (1) Siberian magnetic susceptibility stratigraphy, (2) data recorded from other loess-paleosol successions in China, European Russia, Europe, and North America, (3) North Atlantic ice-rafted detritus, and (4) sea-surface temperatures derived from molecular stratigraphy of marine sediments off the northwest coast of Africa.
Keywords: loess; Siberia; paleoclimate; magnetic susceptibility; Heinrich events